ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DENGAN PENDEKATAN DEEP LEARNING DI SD NEGERI 1 KAUMAN MAGETAN - Palistin, Amnah; Dianti, Noviana Stalis; Muazizah, Nisfatul Latifum; Putri Octaviana, Nanda Ayunda Ika; Excanda Ramadani, Xanza; Indrawati, Delia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Merdeka Curriculum using a deep learning approach at SD Negeri 1 Kauman Magetan. The research employs a qualitative approach with a case study design, where data were collected through in-depth interviews and documentation studies. The results indicate that teachers have integrated the three main principles of deep learning: meaningful learning through contextual strategies, mindful learning through routine reflection activities, and joyful learning through varied methods such as Problem-Based Learning (PBL) and interactive media. This implementation is also oriented towards developing students' 6C competencies. Although effective, the primary challenge identified is the process of shifting students' mindsets from result-oriented to process-oriented, alongside teachers' limited experience with this new approach. Adaptive strategies implemented include thorough planning, collaboration among teachers, and participation in professional workshops. The study concludes that the deep learning approach is capable of realizing more holistic and meaningful learning at the elementary school level.